2008
DOI: 10.3168/jds.2007-0728
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Whole-Farm Model for Pasture-Based Dairy Systems

Abstract: In the temperate climate of New Zealand, animals can be grazed outdoors all year round. The pasture is supplemented with conserved feed, with the amount being determined by seasonal pasture growth, genetics of the herd, and stocking rate. The large number of factors that affect production makes it impractical and expensive to use field trials to explore all the farm system options. A model of an in situ-grazed pasture system has been developed to provide a tool for developing and testing novel farm systems; fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 17 publications
1
49
0
4
Order By: Relevance
“…The accuracy of prediction was moderate for LW and BCS, when considering the CCC (Table 1). These levels of accuracy of prediction for DM intake and milk yield are similar or higher than those reported for other models for grazing dairy systems, such as Farmax Dairy Pro (Bryant et al, 2010), GrazeIn (Delagarde et al, 2011) and the WFM (Beukes et al, 2008). However, it is important to notice that the validation of the model was conducted for annual outputs, and the accuracy of the model for short-term predictions (weekly or monthly basis) remains to be tested.…”
Section: Model Validationsupporting
confidence: 66%
See 1 more Smart Citation
“…The accuracy of prediction was moderate for LW and BCS, when considering the CCC (Table 1). These levels of accuracy of prediction for DM intake and milk yield are similar or higher than those reported for other models for grazing dairy systems, such as Farmax Dairy Pro (Bryant et al, 2010), GrazeIn (Delagarde et al, 2011) and the WFM (Beukes et al, 2008). However, it is important to notice that the validation of the model was conducted for annual outputs, and the accuracy of the model for short-term predictions (weekly or monthly basis) remains to be tested.…”
Section: Model Validationsupporting
confidence: 66%
“…Some of these models work at a herd level (Larcombe, 1990;Freer et al, 1997;Shalloo et al, 2004;Schils et al, 2007;Vayssiè res et al, 2009), whereas other models work at an individual animal level (Beukes et al, 2008;Bryant et al, 2010). These latter models account for genetic differences between cows, but they were designed to be used under specific conditions, that is, grass-based dairy systems and their environmental conditions under which the breeding values were estimated.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, for milksolids production per cow per day, Beukes et al (2008) reported MPEs ranging from 0.23 to 0.52 using the Whole Farm Model, compared with 0.14 to 0.21 in the present evaluation. The Whole Farm Model was more accurate at predicting cow condition score, with an MPE of 0.01 to 0.06 compared with 0.05 to 0.11 in the present evaluation.…”
Section: Discussionmentioning
confidence: 80%
“…Such an approach can be achieved using models that simulate the economic and environmental implications of practices at the farm scale. Recent years have seen the development of several farm-scale models, such as DairyWise in the Netherlands (Schils et al 2007), WFM (Whole-Farm Model) in New Zealand (Wastney et al 2002;Beukes et al 2008), GAMEDE (Global Activity Model for Evaluating the sustainability of Dairy Enterprises) in France (Vayssie`res et al 2009a, b), and the Integrated Farm System Model (IFSM) in the United States (Rotz et al 2014). However, the ability of these models to simulate crop production in northern regions with boreal and hemiboreal climates (Ko¨ppen climate classification; Peel et al 2007), such as eastern Canada, which are characterized by short growing seasons (mid-April to mid-September on average) and long periods of soil freezing and snow cover, needs to be verified.…”
mentioning
confidence: 99%